2016
DOI: 10.1186/s12991-016-0115-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mirtazapine versus selective serotonin reuptake inhibitors on benzodiazepine use in patients with major depressive disorder: a pragmatic, multicenter, open-label, randomized, active-controlled, 24-week trial

Abstract: BackgroundThis study aimed to evaluate whether selecting mirtazapine as the first choice for current depressive episode instead of selective serotonin reuptake inhibitors (SSRIs) reduces benzodiazepine use in patients with major depressive disorder (MDD). We concurrently examined the relationship between clinical responses and serum mature brain-derived neurotrophic factor (BDNF) and its precursor, proBDNF.MethodsWe conducted an open-label randomized trial in routine psychiatric practice settings. Seventy-seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…We found similar results: in animals dosed with 30 mg mirtazapine, anxiety-like (as measured in the EPM test, OFT and the LDT) and depression-like behaviors (according to the FST) decreased after 15 days of treatment. Studies elsewhere have indicated that mirtazapine exerts rapid antidepressant effects compared with drugs such as the SSRIs (Hashimoto et al, 2016;Tsutsumi et al, 2016). Again, our results were similar -after only 15 days of treatment, we noted a decrease in depression-and anxiety-like behaviors.…”
Section: -supporting
confidence: 85%
See 1 more Smart Citation
“…We found similar results: in animals dosed with 30 mg mirtazapine, anxiety-like (as measured in the EPM test, OFT and the LDT) and depression-like behaviors (according to the FST) decreased after 15 days of treatment. Studies elsewhere have indicated that mirtazapine exerts rapid antidepressant effects compared with drugs such as the SSRIs (Hashimoto et al, 2016;Tsutsumi et al, 2016). Again, our results were similar -after only 15 days of treatment, we noted a decrease in depression-and anxiety-like behaviors.…”
Section: -supporting
confidence: 85%
“…Mirtazapine, a tetracyclic antidepressant, is used primarily to treat depression, though it is also sometimes used for anxiety or sleeplessness and other indications (de Boer, 1995(de Boer, , 1996Hashimoto et al, 2016;Tsutsumi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for the depressed patients with clinically significant insomnia, a treatment with a sedative antidepressant is usually more recommended [ 19 ]. It was recently shown that such treatment significantly reduces the need to use benzodiazepines in patients with MDD [ 20 •]. Such an approach, combination treatment with benzodiazepines and SSRI/SNRI is often necessary to reduce anxiety and insomnia as early as in the first week of treatment.…”
Section: Effects On Antidepressants On Sleepmentioning
confidence: 99%
“…Although it is very common for the depressed patient to be prescribed hypnotics or anxiolytics with antidepressants, we did not take this treatment into account in our analysis. However, some studies showed that mirtazapine decreased the use of hypnotics significantly . Therefore, the cost‐effectiveness of mirtazapine might improve further if that impact is considered.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies showed that mirtazapine decreased the use of hypnotics significantly. 44,45 Therefore, the cost-effectiveness of mirtazapine might improve further if that impact is considered.…”
Section: Comparison Of Icers Between Observational Pointsmentioning
confidence: 99%